Best-practice indicators in Psoriatic disease care - Helliwell, P; Favier, G; Gladman, D; Soriano, E; Kirkham, B; Coates, L; Puig, L; Boehncke, W; Thaçi, D (Journal of Rheumatology, 2019)
Objective: In 2016, members of the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA), in collaboration with KPMG LLP (UK), conducted a study to measure care in psoriatic arthritis (PsA). A key finding was that centers do not usually have processes in place to measure the effect of improved quality of care. Our objectives were to identify and select best-practice indicators to enable PsA caregivers to assess and monitor the outcomes of specific initiatives aimed at improving care in 4 focus areas: (1) shortening time to diagnosis; (2) improving multidisciplinary collaboration; (3) optimizing disease management; and (4) improving disease monitoring.